Over-Expression of the LH Receptor Increases Distant Metastases in an Endometrial Cancer Mouse Model - Pillozzi, Serena; Fortunato, Angelo; De Lorenzo, Emanuele; Borrani, Elena; Giachi, Massimo; Scarselli, Gianfranco; Arcangeli, Annarosa; Noci, Ivo (Frontiers in Oncology, 2013)
Objective. The aim of the present study was to define the role of luteinizing hormone receptor (LH-R) expression in endometrial cancer (EC), using preclinical mouse models, to further transfer these data to the clinical setting. Methods. The role of LH-R over-expression was studied using EC cells (Hec1A, e.g. cells with low endogenous LH-R expression) transfected with the LH-R (Hec1A-LH-R). In vitro cell proliferation was measured through the WST1 assay, whereas cell invasion was measured trough the matrigel assay. The effects of LH/hCG-R overexpresion in vivo were analyzed in an appropriately developed preclinical mouse model of EC, which mimicked postmenopausal conditions. The model consisted in an orthotopic xenograft of Hec1A cells into immunodeficient mice treated daily with recombinant LH, to assure high levels of LH. Results. In vitro data indicated that LH-R overexpression increased Hec1A invasiveness. In vivo results showed that tumors arising from Hec1A-LH-R cells injection displayed a higher local invasion and a higher number of distant metastases, mainly in the lung, compared to tumors obtained from the injection of Hec1A cells. LH withdrawl strongly inhibited local and distant metastatic spread of tumors, especially those arising from Hec1A-LH-R cells. Conclusions. The overexpression of the LH-R increases the ability of EC cells to undergo local invasion and metastatic spread. This occurs in the presence of high LH serum concentrations.